Stability Analysis of the New Section in Raising the Existing Composite Wala Dam Using Finite Element Methods - Dima A. Husein Malkawi; Abdallah I. Husein Malkawi (Advances in Civil Engineering)
Jordan is a country with a population that increases steadily but is punctuated by waves of refugees. Henceforth, Jordan will be destabilized with prolonged and potential water shortages. With both climate and population changes, the nation needs to implement comprehensive reform. In many cases, raising the height of an existing dam would help reduce the gap between the sources and water demands. Consequently, the original Wala dam in Jordan with a capacity of 9.3 million cubic meters (MCM) was raised to achieve a capacity of 25 MCM. The Wala dam was raised uniquely and unusually, which raises concerns about its stability and safety. In this paper, a two-dimensional plane strain model was conducted using finite element modeling (FEM) on the Wala dam to investigate the stability conditions of the raised dam. Several material properties were used in this study. These properties are density, Poisson’s ratio, elastic modulus, and friction angle. Stresses and deformations of the new section within the dam body, dam foundation, and an earthfill embankment are presented and compared with the original dam. Results showed that the stresses after raising the height of the dam body are below 1.5 MPa, and it is within the allowable range. Moreover, the stability analysis showed that the stresses and deformation are minimal and negligible. Also, no failure was observed or reported within the soil. Furthermore, a stability analysis of the slip surface of the new body of the dam structure using the finite element method is introduced. Two potential slip surfaces were examined, and a surface-to-surface contact element is modeled to simulate the slip surface. In addition, settlement field observations for 16 months are presented and discussed in this paper.